Rbfox1 Is Expressed in the Mouse Brain in the Form of Multiple Transcript Variants and Contains Functional E Boxes in Its Alternative Promoters - Casanovas, Sonia; Schlichtholz, Laura; Mühlbauer, Sophia; Dewi, Sri; Schüle, Martin; Strand, Dennis; Strand, Susanne; Zografidou, Lea; Winter, Jennifer (Frontiers in Molecular Neuroscience, 2020)
The RNA-binding protein RBFOX1 is an important regulator of neuron development and neuronal excitability. Rbfox1 is a dosage sensitive gene and in both mice and humans, decreased expression of Rbfox1 has been linked to neurodevelopmental disorders. Alternative promoters drive expression of Rbfox1 transcript isoforms that encode an identical protein. The tissue- and developmental stage-specific expression of these isoforms as well as the underlying regulatory mechanisms are, however, unclear. Here, we set out to capture all of the Rbfox1 transcript isoforms and identify transcriptional mechanisms that regulate brain specific Rbfox1 expression. Isoform sequencing identified multiple alternative Rbfox1 transcript variants in the mouse cerebral cortex, including transcripts with novel first exons, alternatively spliced exons and 3'-truncations. Quantitative RT-PCR determined expression of the alternative first exons in the developing cerebral cortex and in different subregions of the juvenile brain. Alternative first exons were found to be highly stage- and subregion specific in their expression patterns suggesting that they fulfill specific functions during cortex development and in different brain regions. Using reporter assays we found that the promoter regions of the two first exons E1B and E1C/E1C.1 contain several functional E-boxes. Together, we provide an extensive picture of Rbfox1 isoform expression. We further identified important regulatory mechanisms that drive neuron specific Rbfox1 expression. Thus, our study forms the basis for further research into the mechanisms that ensure physiological Rbfox1 expression in the brain. It also helps to understand why, in patients with neurodevelopmental disorders deletion of individual RBFOX1 transcript isoforms could affect brain function.